Cuidados de enfermería y manejo del dolor en fracturas expuestas de tibia-peroné: una revisión sistemática - Pacha Orozco, Mayra Alexandra (2026)
Open fractures of the tibia and fibula are among the most frequent and complex traumatic injuries both nationally and internationally, with a high incidence of infectious complications and severe pain. This study aimed to standardize nursing care and pain management strategies in adult patients with open tibia-fibula fractures, evaluating their effectiveness in recovery and complication prevention. A systematic review was conducted using the PRISMA methodology, selecting 24 scientific articles from international and regional databases focused on nursing interventions, pain management, and infection prevention. The results showed that the rigorous application of antiseptic protocols, timely administration of prophylactic antibiotics, and maintenance of a sterile environment significantly reduce the incidence of postoperative infections and improve clinical outcomes, shortening hospitalization times. Additionally, the use of validated pain assessment scales and the continuous training of nursing staff were essential to optimize care and functional recovery. It is concluded that the standardization of care and a comprehensive approach to pain management are key to the efficient and safe recovery of patients with open tibia-fibula fractures.